Biomechanics of aggressive inline skating: Landing and balancing on a grind rail - Major, M. J.; Beaudoin, A. J.; Kurath, P.; Hsiao-Wecksler, E. T. (Journal of Sports Sciences, 2007)
Currently, only epidemiological injury data have been reported for the new extreme sport of aggressive inline skating, or trick skating. No studies have examined the biomechanics of this sport, which involves repetitive jumping and landing from railings, ramps, and ledges, often over 1 m in height. We present results of a pilot study that examined the effect of skater experience and lower extremity biomechanics on energy absorption ability, and observed balance strategies used during two basic tricks. In these tricks, the skater jumps onto an elevated rail and maintains balance while standing in a single position (stall) or sliding along the rail (grind). Lower extremity joint kinematics, impact force characteristics, and general movement behaviours were examined during landing and balance phases. Ten male skaters performed ten stalls and ten frontside grinds on an instrumented grind rail, capable of measuring vertical force. Vertical impact force was found to decrease with increasing skater experience in stalls (r = -0.84, P = 0.002) and grinds (r = -0.84, P = 0.009). This might imply that less-experienced skaters are (subconsciously) more concerned about maintaining balance than refining technique to minimize impact force. Similar to drop landing experiments, peak impact force decreased with increasing knee flexion during stalls (r = -0.65, P = 0.04). During stalls, skaters demonstrated classic balance maintenance strategies (ankle, hip, or multi-joint) depending on trick length. During grinds, skater centre of mass never passed over the rail base of support, suggesting the use of momentum produced from obliquely approaching the rail.